2017
DOI: 10.1016/j.jtho.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial of Erlotinib versus Docetaxel in Patients with Advanced Squamous Cell Non–Small Cell Lung Cancer Failing First-Line Platinum-Based Doublet Chemotherapy Stratified by VeriStrat Good versus VeriStrat Poor. The European Thoracic Oncology Platform (ETOP) EMPHASIS-lung Trial

Abstract: The final analysis of EMPHASIS-lung did not show a differential effect on PFS for erlotinib versus docetaxel stratified by VeriStrat status. Similarly, in the combined analysis, no significant treatment by VeriStrat status interaction was observed (interaction p = 0.24 for PFS and 0.45 for OS, stratified by study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…11,12 In the CTONG0806 study, pemetrexed was administered as second‐line treatment in advanced non‐squamous NSCLC patients with wild‐type EGFR and the mPFS was 4.8 months . The ETOP study showed an mPFS of 4.1 months in advanced squamous cell NSCLC patients treated with docetaxel as second‐line setting . In our patient sample, the mPFS in squamous cell NSCLC patients was 5.5 months (95% CI 0–12.7) and in adenocarcinoma NSCLC patients 6.3 months (95% CI 0–12.8) as a second‐line setting.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…11,12 In the CTONG0806 study, pemetrexed was administered as second‐line treatment in advanced non‐squamous NSCLC patients with wild‐type EGFR and the mPFS was 4.8 months . The ETOP study showed an mPFS of 4.1 months in advanced squamous cell NSCLC patients treated with docetaxel as second‐line setting . In our patient sample, the mPFS in squamous cell NSCLC patients was 5.5 months (95% CI 0–12.7) and in adenocarcinoma NSCLC patients 6.3 months (95% CI 0–12.8) as a second‐line setting.…”
Section: Introductionmentioning
confidence: 72%
“…For advanced NSCLC patients with or without EGFR mutations, EGFR‐tyrosine kinase inhibitors (TKIs) and chemotherapy are recommended as first‐line treatment, respectively . After the failure of first‐line therapy, second or third‐line treatment does not currently yield acceptable progression‐free‐survival (PFS) or overall survival (OS) . Third‐generation EGFR‐TKIs were not available in mainland China at the beginning of our research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VeriStrat test is also predictive for outcomes to epidermal growth factor receptor ( EGFR )‐targeted therapies in patient cohorts in whom the EGFR mutation status is wild type (WT) or unknown. Multiple studies have demonstrated that VeriStrat testing can predict outcome to erlotinib , gefitinib , and cetuximab , either as monotherapy or in combination with other treatments . A retrospective analysis of the LUX‐lung 8 study demonstrated that VeriStrat could also predict OS in patients with squamous cell carcinoma treated with afatinib (VS‐G median OS, 11.5 mo; VS‐P median OS, 4.7 mo; HR, 0.57; p = .0001) .…”
Section: Introductionmentioning
confidence: 99%
“…VeriStrat status can indicate the likelihood of a favorable or unfavorable prognosis, and may also predict treatment outcomes. Potential clinical utility of the VeriStrat test in NSCLC has been exhibited across a range of EGFR-targeted agents [17][18][19][20][21][22][23]. For example, in the phase III PROSE study, the VeriStrat test has shown prognostic and predictive utility for second-line erlotinib in patients with NSCLC, most of whom had wildtype or unknown EGFR mutation status [22].…”
Section: Introductionmentioning
confidence: 99%